2018
DOI: 10.1038/s41598-018-34754-4
|View full text |Cite
|
Sign up to set email alerts
|

Pili mediated intercellular forces shape heterogeneous bacterial microcolonies prior to multicellular differentiation

Abstract: Microcolonies are aggregates of a few dozen to a few thousand cells exhibited by many bacteria. The formation of microcolonies is a crucial step towards the formation of more mature bacterial communities known as biofilms, but also marks a significant change in bacterial physiology. Within a microcolony, bacteria forgo a single cell lifestyle for a communal lifestyle hallmarked by high cell density and physical interactions between cells potentially altering their behaviour. It is thus crucial to understand ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Moreover, in the recent bioremediation studies, it is becoming increasingly clear that the biological "platforms" are advantageous to the inorganic surfaces as a source of nutrients and a physical barrier, which simultaneously enhances the PGP properties of the bacteria [34]. In this study, we observed bacterial microcolonies in the intercellular crevices between epidermal root cells, which is a form of bacterial organization known to correspond to the early stages of biofilm formation [35]. The root exudates tend to leak from these intercellular spaces, therefore attracting the bacteria, which subsequently tend to organize into microcolonies and fully-formed biofilms [21,28,35].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, in the recent bioremediation studies, it is becoming increasingly clear that the biological "platforms" are advantageous to the inorganic surfaces as a source of nutrients and a physical barrier, which simultaneously enhances the PGP properties of the bacteria [34]. In this study, we observed bacterial microcolonies in the intercellular crevices between epidermal root cells, which is a form of bacterial organization known to correspond to the early stages of biofilm formation [35]. The root exudates tend to leak from these intercellular spaces, therefore attracting the bacteria, which subsequently tend to organize into microcolonies and fully-formed biofilms [21,28,35].…”
Section: Discussionmentioning
confidence: 63%
“…In this study, we observed bacterial microcolonies in the intercellular crevices between epidermal root cells, which is a form of bacterial organization known to correspond to the early stages of biofilm formation [35]. The root exudates tend to leak from these intercellular spaces, therefore attracting the bacteria, which subsequently tend to organize into microcolonies and fully-formed biofilms [21,28,35]. This is a property that is reported to be useful in very different bioremediation strategies [25,35].…”
Section: Discussionmentioning
confidence: 83%
“…Pili-mediated intercellular interactions of the bacteria are well studied and may serve as an important example to construct a microscopic model for active cellular force generation. N. gonorrhoeae bacteria have multiple (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) pili isotropically distributed over the cell body (see fig. 1 (c)) [27][28][29].…”
Section: A Pili-mediated Forcesmentioning
confidence: 99%
“…Multi-scale computer simulations have played an important role in the study of the physics of the formation of N. gonorrhoeae colonies [16][17][18]. Continuum approaches such as theories of active gels [19][20][21][22][23][24][25][26] so far do not capture important features of dense cellular aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, motility can either favor bacterial aggregation by enabling cell-cell encounters [15] but also prevent localized aggregates by enhancing dispersion [18]. Moreover, it is well-known that bacteria develop several subpopulations in order to adapt to evolving environmental conditions [19], so that heterogeneous behaviours can be found inside colonies [20,21]. But how heterogeneity influences clustering in such real systems is presently unknown.…”
Section: Introductionmentioning
confidence: 99%